Development of an acceptable chicken loaf recipe (2007)
This product development research aimed to develop a protein dish out of chicken. The chicken was processed into a loaf. the product was tested and re-tested until acceptable proportion was achieved. The level of acceptability of the chicken loaf was evaluated in terms of appearance, aroma, texture, flavor and general acceptability utilizing the sensory score sheet prepared by the researchers. Sixty members constituted the panel of tasters composed of faculty and staff, students and housewives who were selected purposely for this study. The data were analyzed and interpreted using mean as the statistical tool. Results showed that the chicken loaf was liked very much by the respondents in terms of appearance (4.26), aroma (4.21), texture (4.11), flavor (4.23) and liked extremely in terms of general acceptability (4.32). Laboratory analysis for proximate composition of chicken loaf showed the following results: protein, 11.45 percent; lipids, 8.74 percent; moisture, 66.73 percent; and ash, 2.55 percent. The cost of one chicken loaf was Php 64.95. Since chicken loaf was liked very much, it is recommended that results be disseminated to the consuming public and food study be conducted to test the shelf-life of the chicken loaf.
Keywords: Cooking (Chicken)